2017
DOI: 10.5546/aap.2017.eng.54
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation, periodic breathing, and sleep apnea in infants aged 1-4 months old living at 3200 meters above sea level

Abstract: Objectives:To describe, in infants aged 1-4 months old living at 3200 meters above sea level (MASL), oxygen saturation (SpO 2 ), sleep apnea indices, and periodic breathing (PB) during sleep. Polysomnographies were done in 18 healthy infants. Results: The median SpO 2 was 87%, and the median PB was 7.2% for the total sleep time. The median central sleep apnea index was 30.5/hour, which decreased to 5.4/hour once sleep apneas associated with PB were excluded. The 5 th percentile for SpO 2 was 76% among awake in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In this study, we describe obstructive and central respiratory events as well as gaseous exchange measures of oxygen saturation indices and transcutaneous CO 2 measurements in 32 healthy non-snoring children aged 4 to 9 years living at 2,560 m a. s. l. Our results show that the median AHI was 10.2 times higher than normal values established at sea level for children 3-5 years old and 13.5 times higher than for children aged 6-7 years (Montgomery-Downs et al, 2006). This increase among children living at moderate to high altitude has already been reported in several studies (Burg et al, 2013;Duenas-Meza et al, 2015;Ucrós et al 2015, Ucrós et al 2017 and can be attributed to two potential mechanisms: firstly, due to a primarily obstructive breathing pattern as demonstrated by the current study and also observed in a study carried out at 3,200 m a. s. l. in 7-to 16-year-old children in Bolivia ; secondly, exclusively due to central events, as reported in a study conducted on preschoolers (3-5 years old) living at 1,600 m a. s. l. in Denver, USA (Burg et al, 2013). The predominance of central events found in Denver was not seen in studies in Bolivia or in the current study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, we describe obstructive and central respiratory events as well as gaseous exchange measures of oxygen saturation indices and transcutaneous CO 2 measurements in 32 healthy non-snoring children aged 4 to 9 years living at 2,560 m a. s. l. Our results show that the median AHI was 10.2 times higher than normal values established at sea level for children 3-5 years old and 13.5 times higher than for children aged 6-7 years (Montgomery-Downs et al, 2006). This increase among children living at moderate to high altitude has already been reported in several studies (Burg et al, 2013;Duenas-Meza et al, 2015;Ucrós et al 2015, Ucrós et al 2017 and can be attributed to two potential mechanisms: firstly, due to a primarily obstructive breathing pattern as demonstrated by the current study and also observed in a study carried out at 3,200 m a. s. l. in 7-to 16-year-old children in Bolivia ; secondly, exclusively due to central events, as reported in a study conducted on preschoolers (3-5 years old) living at 1,600 m a. s. l. in Denver, USA (Burg et al, 2013). The predominance of central events found in Denver was not seen in studies in Bolivia or in the current study.…”
Section: Discussionsupporting
confidence: 79%
“…OAHI and ODI recommended by European and American guidelines are derived from studies conducted at sea level (Chan et al, 2004;Kaditis et al, 2016;Uliel et al, 2004), which cannot be extrapolated to people living at high altitudes. In such locations, respiratory sleep physiology in children and adults is different (Burg et al, 2013;Duenas-Meza et al, 2015;Pham et al, 2017;San et al, 2013;Ucrós et al, 2015;Ucrós., et al 2017). It has been shown that at 3,200 m above sea level (m a.s.l.)…”
mentioning
confidence: 99%
“…This is probably related to central nervous system (CNS) maturation ( 3 ). However, in young infants living at high altitude, the percentage of PB is higher in comparison with low altitude ( 5 , 6 , 8 ). It has been suggested that some individuals are prone to PB because CNS oxygen receptors have increased chemosensivity to hypoxia ( 15 ).…”
Section: Discussionmentioning
confidence: 88%
“…In a study of neonates born at altitudes of 1,371–2,484 meters, Ravert et al found no significant differences in SpO 2 values measured at different resting states ( 21 ). However, a study on infants aged 1–4 months living at 3,200 meters altitude did find differences in SpO 2 recorded during awake vs. sleeping states ( 25 ). Whether the contradictory results are due to differences in altitude or differences in the ages of the study participants is unclear.…”
Section: Discussionmentioning
confidence: 99%